Understanding Low Empathy and Reluctance to Share Among Young Children : A Qualitative Analysis - Efna Leluni; Novitawati Novitawati; Yogi Prihandoko (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Empathy and sharing are essential foundations in shaping the social character of early childhood, as they play a crucial role in fostering compassion, cooperation, and the ability to build positive relationships with others. However, in practice, many behaviors among young children still reflect a low level of empathy, such as reluctance to share toys, competing for play materials, and being insensitive to peers’ feelings. This study aims to analyze the symptoms of low empathy and sharing attitudes among early childhood learners through observational approaches in preschool settings. The research employed a descriptive qualitative method using non-participant observation and informal interviews with classroom teachers. The findings revealed that egocentric behavior in children tends to arise from a lack of habituation, limited social simulation, and insufficient positive reinforcement within the learning environment. This study emphasizes the importance of implementing consistent and collaborative social-emotional learning strategies between teachers and parents to nurture empathy and sharing attitudes in young children.